Leadership Style on Health Worker Performance in Primary Health Facilities - Siregar, Jelita Suryani; Febrina, Dea; Diwanta, Faradilla; Marwa, Nabilah Aprilia; Harahap, Rosida Sapriani; Maghfirah, Suci; Wasiyem, Wasiyem (Universitas Ibn Khaldun Bogor, 2025)
Leadership style on health worker performance emphasizes the importance of health worker performance in ensuring service quality, as well as the various challenges faced. Data were collected from various literature sources relevant to this study through the library study method. The results of the discussion indicate that transformational and participatory leadership styles have a positive effect on the motivation and performance of health workers , while authoritarian styles can hinder innovation even though they are effective in certain situations. This study found that work motivation and work environment act as mediators between leadership style and performance. The conclusion at the end of the study confirms that the application of an inclusive and collaborative leadership style is very important to improve the performance of health workers, and encourages further research to explore this relationship in depth.